Brain Endothelium: The “Innate Immunity Response Hypothesis” in Cerebral Malaria Pathogenesis - Pais, Teresa F.; Penha-Gonçalves, Carlos (Frontiers in Immunology, 2019)
Cerebral malaria (CM) is a life-threatening neurological syndrome caused by Plasmodium falciparum infection that afflicts mainly children in Africa. Current patho-physiology models implicate parasite and host-derived factors in impairing the barrier function of brain blood vessels. Leakage of fluids and proteins into the brain parenchyma with subsequent brain swelling is the most probable cause of death in CM. It is well established that brain endothelial cells (BECs), in particular those lining the microvasculature are targets of infected red blood cells adherence (e.g. binding to the endothelial protein C receptor, EPCR) and immune mediators (e.g. TNF, IL1-β, INF-γ) that promote endothelium activation. Activated BECs take part in amplifying localized inflammatory reactions leading to microcirculatory and coagulation disturbances and to altered vascular permeability impairing blood–brain barrier (BBB) integrity. Yet, the role of BECs as initiators of immune responses against parasite molecules and infected red blood cells is underexplored. BECs express pattern recognition receptors (PPR) and are privileged sensors of early blood changes induced by infection. Here we focus on the hypothesis that innate responses initiated by BECs and subsequent interactions with immune cells are critical to trigger effector immune functions in CM development. Research on mechanisms used by BECs in innate immune sensing and in directing adaptive immune responses in the interface between the immune and the nervous system could reveal immunomodulatory targets for adjuvant therapies to prevent and control CM development.